2022
DOI: 10.3390/ijms23116080
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of MultiTEP-Platform-Based Recombinant Protein Vaccine, PV-1950R, Targeting Three B-Cell Antigenic Determinants of Pathological α-Synuclein

Abstract: Parkinson’s disease (PD) and dementia with Lewy bodies (DLB) are characterized by the aberrant accumulation of intracytoplasmic misfolded and aggregated α-synuclein (α-Syn), resulting in neurodegeneration associated with inflammation. The propagation of α-Syn aggregates from cell to cell is implicated in the spreading of pathological α-Syn in the brain and disease progression. We and others demonstrated that antibodies generated after active and passive vaccinations could inhibit the propagation of pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Recent studies have also evaluated the immunogenicity of a recombinant DNA vaccine to multiple B-cell epitopes of α-syn, PV-1950R, that was able to reduce total and protein-kinase-resistant α-syn [ 67 , 68 ]. Hence, active immunotherapy may prove a useful means to limit toxic α-syn accumulation and the pathological consequences that arise from its neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also evaluated the immunogenicity of a recombinant DNA vaccine to multiple B-cell epitopes of α-syn, PV-1950R, that was able to reduce total and protein-kinase-resistant α-syn [ 67 , 68 ]. Hence, active immunotherapy may prove a useful means to limit toxic α-syn accumulation and the pathological consequences that arise from its neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve robust and reliable immunogenicity, we applied our well-characterized universal vaccine platform MultiTEP, which is currently being evaluated in multiple preclinical IND enabling studies [ 42 , 43 , 44 , 46 , 68 ] and is in a first-in-human DNA vaccine Phase I clinical trial (NCT05642429). This vaccine platform is designed to induce strong immune responses in genetically diverse populations and potentially in immunosenescence individuals by activating pre-existing memory T helper cells with select universal foreign T helper (Th) epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that antibodies generated after active and passive vaccinations can inhibit the spread of pathological α-syn in the extracellular space and prevent or inhibit diseases in relevant animal models. The brief report by Zagorski and collaborators [ 58 ] published in this Special Issue developed a recombinant protein-based MultiTEP vaccine and tested its immunogenicity in young and aged D-line mice.…”
Section: An Overview Of the Published Articlesmentioning
confidence: 99%